2016
DOI: 10.1590/1678-4685-gmb-2014-0300
|View full text |Cite
|
Sign up to set email alerts
|

The PIN1 family gene PvPIN1 is involved in auxin-dependent root emergence and tillering in switchgrass

Abstract: Switchgrass (Panicum virgatum L.; family Poaceae) is a warm-season C4 perennial grass. Tillering plays an important role in determining the morphology of aboveground parts and the final biomass yield of switchgrass. Auxin distribution in plants can affect a variety of important growth and developmental processes, including the regulation of shoot and root branching, plant resistance and biological yield. Auxin transport and gradients in plants are mediated by influx and efflux carriers. PvPIN1, a switchgrass P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Previous reports have also implicated SA in the regulation of the biosynthesis, transport and signaling of auxin, which acts as important regulator of tiller formation/branching in plants. For example, SA represses the expression of genes encoding auxin receptor (TIR1) and auxin importer and exporter (AUX1 and PIN7) [38], and such suppression of auxin transport and signaling has been shown to lead to an increase in the number of tillers [39,40]. Therefore, the prevalence of enhanced tiller formation in response to SA might suggest the suppression of auxin production/signaling and its transport.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have also implicated SA in the regulation of the biosynthesis, transport and signaling of auxin, which acts as important regulator of tiller formation/branching in plants. For example, SA represses the expression of genes encoding auxin receptor (TIR1) and auxin importer and exporter (AUX1 and PIN7) [38], and such suppression of auxin transport and signaling has been shown to lead to an increase in the number of tillers [39,40]. Therefore, the prevalence of enhanced tiller formation in response to SA might suggest the suppression of auxin production/signaling and its transport.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive tiller in cereal crop can lead to yield reductions because tillers compete for resources, and many secondary tillers are not fertile [31]. PIN1 genes play roles in the regulation of tiller number and tiller angle in rice [21] and switchgrass [17]. In this study, we found that the down-expression of TaPIN1s significantly increased tiller numbers at the tillering stage, jointing stage, and mature stage in wheat.…”
Section: Discussionmentioning
confidence: 57%
“…The initiation and growth of lateral branches (called tillers in grasses) are important factors in determining plant architecture and yield [12][13][14]. Previous studies have demonstrated that decreased auxin transport affects branching in the monocot plants, such as rice, maize, and switchgrass (Panicum virgatum) [15][16][17]. Auxin maxima created by PIN1 at the meristem surface are responsible for organ initiation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive tiller in cereal crop can lead to yield reductions because tillers compete for resources, and many secondary tillers are not fertile [ 31 ]. PIN1 genes play roles in the regulation of tiller number and tiller angle in rice [ 21 ] and switchgrass [ 17 ]. In this study, we found that the down-expression of TaPIN1s significantly increased tiller number at the tillering stage, jointing stage, and mature stage in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation and growth of lateral branches (called tillers in grasses) are important factors in determining plant architecture and yield [ 12 14 ]. Previous studies have demonstrated that decreased auxin transport affects branching in the monocot plants, such as rice ( Oryza sativa ), maize ( Zea mays ), and switchgrass ( Panicum virgatum ) [ 15 17 ]. Auxin maxima created by PIN1 at the meristem surface are responsible for organ initiation [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%